2004
DOI: 10.1016/j.jacc.2004.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angioplasty in Acute Myocardial Infarction at Hospitals With No Surgery On-Site (the PAMI-No SOS study) versus transfer to surgical centers for primary angioplasty

Abstract: On-site PA and transfer groups had similar 30-day outcomes and more rapid reperfusion for on-site PA. Primary angioplasty in high-risk AMI patients at hospitals with No SOS is safe, effective, and faster than PA after transfer to a surgical facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 27 publications
(21 reference statements)
0
47
0
Order By: Relevance
“…[11][12][13][14] In addition, a multi-center study has indicated that although primary PCI without on-site cardiac surgery and transfer to surgical centers for PCI had similar 30-day outcomes, there was a mean delay in primary PCI of approximately 60 min for the transfer to surgical centers. 5 The survival benefit from primary PCI decreases as the time delay to PCI increases, and according to a previous report, this advantage might disappear when the time delay to PCI is more than 60 min compared with the time to administration of thrombolytic agents. 15 Moreover, the AMI patients with critical condition, such as congestive heart failure or cardiogenic shock, who might benefit the most from primary PCI, tend to be severely unstable for transfer.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[11][12][13][14] In addition, a multi-center study has indicated that although primary PCI without on-site cardiac surgery and transfer to surgical centers for PCI had similar 30-day outcomes, there was a mean delay in primary PCI of approximately 60 min for the transfer to surgical centers. 5 The survival benefit from primary PCI decreases as the time delay to PCI increases, and according to a previous report, this advantage might disappear when the time delay to PCI is more than 60 min compared with the time to administration of thrombolytic agents. 15 Moreover, the AMI patients with critical condition, such as congestive heart failure or cardiogenic shock, who might benefit the most from primary PCI, tend to be severely unstable for transfer.…”
Section: Discussionmentioning
confidence: 83%
“…Many recent reports from investigators from the USA have shown that centers without and with on-site CABG surgery had similar outcomes for primary PCI, consistent with the present report. [3][4][5][6] However, according to the guidelines for PCI published by the American Heart Association, the American College of Cardiology, and the Society for Cardiovascular Angiography and Interventions in 2005, primary PCI for ST-segment elevation AMI without on-site cardiac surgery is classified as a class IIb indication (usefulness/efficacy is less well established by evidence/opinion) in the conditions in which experienced interventionalists, an experienced catheterization team and a well-equipped catheterization center as well as a proven system for rapid transport to a nearby hospital with CABG surgery are prepared. 10 Increasing body of evidence including our present report might progress this classification to a class IIa (weight of evidence/opinion is in favor of usefulness/efficacy) in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Wharton describes the experience with primary angioplasty for high-risk acute myocardial infarction performed by experienced interventionalists at hospitals with no cardiac surgery on-site. 7 The requirements for the clinical setting included an experienced interventionalist who performed elective interventions in a surgical centre, an experienced team on a 24 hours a day, seven days a week call schedule, a well-equipped cath lab facility and written transfer protocols. Ting recently reported the clinical outcomes in 1007 elective PCI and primary PCI in a community hospital without on-site cardiac surgery compared with those at a centre with on-site cardiac surgery.…”
Section: Clinical Settingmentioning
confidence: 99%
“…5,6 Several hospitals without on-site cardiac surgical programs have reported their results with PCI. [7][8][9][10][11] Despite satisfactory PCI outcomes at selected centers without surgical backup, concerns remain regarding the implementation of a program that ensures safety, efficacy, and outcomes comparable to those obtained at centers with on-site surgical programs. First, most data are limited to small, single-center observational registries, and data from more than 1 center are urgently needed to demonstrate wider generalizability.…”
mentioning
confidence: 99%